ANALISIS HUBUNGAN HASIL BELAJAR GEOMETRI BIDANG DENGAN KEMAMPUAN ANALITIS MAHASISWA PADA MATA KULIAH GEOMETRI ANALITIK BIDANG - Susanto, Hari Purnomo; Meifiani, Nely Indra; Hidayat, Taufik (Media Pendidikan Matematika, 2017)
This article is a result of research that aims to determine the correlation between students' geometry learning outcomes with analytical ability in the eyes of analytic geometry. This research is a correlational research. the study was conducted at STKIP PGRI Pacitan, where the population is a mathematics education students who is taking analytical geometry courses. Data were taken from 21 students, with test technique, documentation and interview. Data analysis was done by using simple linear regression analysis concept and its calculation using SPSS 16. Based on data analysis, it was found that the result of geometry of field study had positive correlation with students' analytical thinking ability. The relationship falls into the medium category, and the learning outcomes have a predictor contribution to students' analytical ability of 22.5%.